PEMBELAJARAN MAHARAH BAHASA ARAB BERBASIS INKLUSIF - ABDAL CHAQIL HARIMI (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Learning of language is made for students to dominate four skills of language. The skills of language consists of listening skill, speaking skill, reading skill, and writing skill. Therefore, learning of arabic skills must be done well to get goal of learning. A teacher should have a sensitivity in class fo making inklusive class and making class mor fair for student with dissabilities. This articel tries to give many variations for learning of skills for student with dissabilities, esspecially for blind student which obtained from experiences and teorities to make inklusive class. So that, the modification of learning is hoped to make easier for blind student